Effectiveness of class 1 biological safety cabinet modification on reducing air germ rate - Budi Setiawan; Befani Adhitya Febriana; Budi Martono; Saptono Putro (PUINOVAKESMAS, 2021)
Biological Safety Cabinet (BSC) in the form of a ventilated cupboard using a combination of High-Efficiency Particulate Air (HEPA) filtration system, laminar airflow, and containment to protect laboratory, product, and the environment from harmful biological agents. This research aims to determine the effect of level 1 BSC created to decrease the number of air germs in the laboratory. This study was an observational analytic using a cohort design. The research object is the number of air germs in standard Level 1 BSC Safe-tech ES 199 models and level 1 BSC created from a team in the laboratory. Data analysis using one-way ANOVA and independent t-test. One-way ANOVA test data shows the standard level 1 BSC Safe-tech ES 199 models and the creation of level 1 BSC used in 60 minutes and 90 minutes is the same as significant (p>0.05), while the duration of use for 120 minutes has a significant difference (p<0.05). Independent t-test analysis showed Sig (2-tailed) = 0.577, so there were no differences between the two tools during the 120-minute use. The creation of level 1 BSC can reduce the number of air germs.